Dependence of RF breakdown curve on electrode geometry in CCP reactor - Dudin, S.V.; Dakhov, A.N.; Lisovskiy, V.A.; Pletniov, V.M. (Вопросы атомной науки и техники, 2012)
The results of experimental and theoretical study of RF capacitively coupled discharge breakdown in reactor for reactive ion etching of semiconductors are presented. Taking into account complex geometry of the reactor with asymmetric electrodes the main attention has been paid to influence of geometric factor on the breakdown curve. Experiments have shown that the geometry of the electrodes has impact on the breakdown curve only at lowest gas pressure (<50 mTorr). In cylindrical configuration the curve has a region of ambiguity, while for asymmetric configuration similar to GEC reference cell the low pressure part of the breakdown curve is almost vertical. The experimental data are compared to the numerical simulation results obtained using the particle-in-cell/Monte Carlo (PIC/MCC) code. The comparison shows qualitative consistence of the results with general tendency of theoretical curves to be slightly shifted to higher pressures that can be explained by simultaneous action of different kinds of electron emission from the electrodes, while we accounted only for secondary electron emission. Both theory and experiment show influence of secondary electron yield from different electrode materials (aluminum, steel, graphite) on the low-pressure part of the breakdown curve. Представлены результаты экспериментальных и теоретических исследований кривой зажигания ВЧ-разряда в реакторе для ионного реактивного травления. С учетом сложной геометрии реактора с асимметричными электродами основное внимание было уделено влиянию геометрического фактора на кривую зажигания разряда. Эксперименты показали, что геометрия электродов оказывает существенное влияние на кривую зажигания в области низких давлений рабочего газа (<50 мТорр). Для цилиндрической геометрии камеры в области низких давлений существует область неоднозначности кривой зажигания, в то время как для асимметричной конфигурации близкой к GEC ячейке наблюдается практически вертикальный рост напряжения зажигания разряда с уменьшением давления газа. Наблюдается качественное согласие численых расчетов, полученых с использованием particle-in-cell/Monte Carlo (PIC/MCC) кода, с экспериментом. Общую тенденцию смещения рассчетных кривых зажигания в область более высоких давлений можно объяснить необходимостью корректного учета различных видов электронной эмиссии с электродов вдополнение к учтенной нами вторичной е-е-эмиссии. И теория, и эксперимент показывают существенное влияние вторичной элетронной эмиссии на кривую зажигания ВЧ-разряда в области низких давлений. Представлені результати експериментальних та теоретичних досліджень кривої запалювання ВЧ-разряду в реакторi для іонного реактивного травлення. З урахуванням складної геометрії реактора з асиметричними електродами основну увагу було приділено впливу геометричного фактора на криву запалювання розряду. Експерименти показали, що геометрія електродів робить істотний вплив на криву запалювання в області низьких тисків робочого газу (<50 мТорр). Для циліндричної геометрії камери в області низьких тисків існує область неоднозначності кривої запалювання, в той час як для асиметричної конфігурації близької до GEC осередку спостерігається практично вертикальне зростання напруги запалювання розряду при зменшенні тиску газу. Спостерігається якісна згода чисельних розрахункiв, отриманих з використанням particle-in-cell/Monte Carlo (PIC / MCC) коду, з експериментом. Загальну тенденцію зсуву розрахункових кривих запалювання в область більш високих тисків можна пояснити необхідністю коректного врахування різних видів електронної емісії з електродів в доповнення до врахованої нами вторинної е-е-емісії. Як теорія, так і експеримент показують істотний вплив вторинної елетронній емісії на криву запалювання ВЧ-розряду в області низьких тисків.